Income tax law in the Commonwealth Caribbean - Denbow, Claude H. (Butterworths LondonGB, 1997)
Encompasses the historical background of the law in Commonwealth Caribbean countries; the concept and computation of income; the construction and scope of the taxing statutes; the incidence of the tax; powers of the Revenue vis a is the taxpayer; the taxpayer's rights of objection and appeal; and, the role of the courts for recourse by both the taxpayer and the Revenue.